Typological Mistakes Made by Students in Learning the German Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Since Uzbek and German are languages ​​belonging to different language families, it is very difficult for Uzbek students to learn German as a foreign language, especially for the Uzbek audience to master German lexicology and grammar well. In particular, we found out that in the process of learning German as a foreign language, especially when entering into oral communication in German, an Uzbek student makes the following typological mistakes: